FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA UMKM DI KOTA MALANG - Muissu Amina; Moh. Amin; Siti Aminah Anwar (Universitas Islam Malang, 2021)
This research was conducted with the aim of knowing the effect of user involvement, personal skills, training and education, as well as top management on the performance of the Accounting Information System at UMKM in Malang City. This research is a descriptive quantitative type because it explains the results of statistical tests. Sampling in this study is UMKM registered in Diskopindag Malang City by using the calculation of the formula Slovin, so it can be known to have 84 respondents. The data source in this study is primary data by distributing questionnaires and measuring the Likert scale. Based on the results of various tests in this study, it can be concluded that, simultaneously and partially user involvement, personal skills, training and education, and top management have a significant positive effect on the performance of the accounting information system.Keywords: User Involvement, Personal Skills, Training and Education, Top Management, and Accounting Information System Performance.